EFFECT OF SOME ACTIVE STIMULANTS ON PLANT GROWTH, TUBERS YIELD AND NUTRITIONAL VALUES OF POTATO PLANTS GROWN IN NEWLY RECLAIMED SOIL - A. M. Shaheen; M. E. Ragab; Fatma A. Rizk; S. H. Mahmoud1; M. M. Soliman; Nadia M. Omar (Journal of Animal and Plant Sciences, 2019)
Growth stimulants have the ability to stimulate growth of roots, shoots and leaves consequently enhanced yield components of various vegetable crops. Therefore, two field experiments were conducted during seasons of 2012/2013 and 2013/2014 under newly reclaimed sandy soil conditions at a private farm (Taba farm), Sadat city, Egypt. In order tostudy the effect of foliar application of some plant growth stimulants (amino acid, 2.5 cm3/l, chitosan, 5 cm3/l, potassium silicate, 2 cm3/land control treatment), for 3 times in 10 days interval starting at 40 days after planting date, on growth and productivity of potato plants cv. Diamonte. The experiments of a complete randomized block design with four replicates were used. The obtained results indicated that foliar spraying by amino acids mixture or chitosan at rate of 2.5 and 5.0 cm3/l, respectively, gained significantly vigorous plant growth at all sampling dates, 70, 80 and 90 days after planting date, expressed as plant height, number of leaves/plant, number of shoots/plant, fresh weight and dry weight of potato plant and its leaves and shoots, leaf area, leaf area index, relative growth rate and net assimilation rate. Furthermore, foliar spraying of potato plant by amino acids mixture or chitosan resulted in the heaviest total and marketable tuber yield as well as the lowest value of un-marketable yield. The contents of starch, total carbohydrates, total sugar, dry matter, N, P, K, Ca, Fe, Mn, Zn and Cu, all of them recorded a superior with potato plants sprayed by the plant growth stimulant substances compared with those of control. Foliar spraying of amino acids mixture (2.5 cm3/l)or chitosan (5.0 cm3/l) was the most efficient treatment in improving plant vegetative growth, tubers yield and yield quality parameters.
Keywords: Potato; Stimulant substances; Relative growth rate; Net assimilation rate; Vegetative growth; Tuber yield and Yieldquality properties